2021
DOI: 10.3389/fphar.2021.770329
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Anti-Inflammatory Effect of Pterostilbene Against Cerebral Ischemia/Reperfusion Injury via Suppression of COX-2

Abstract: Background: The incidence of cerebral ischemia disease leading cause of death in human population worldwide. Treatment of cerebral ischemia remains a clinical challenge for researchers and mechanisms of cerebral ischemia remain unknown. During the cerebral ischemia, inflammatory reaction and oxidative stress plays an important role. The current investigation scrutinized the neuroprotective and anti-inflammatory role of pterostilbene against cerebral ischemia in middle cerebral artery occlusion (MCAO) rodent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 69 publications
(61 reference statements)
1
18
0
Order By: Relevance
“…The lack of any toxics effects of Ptb fluorescent derivatives ( 1 , 2 ) raised the question if these compounds still maintain some of neuro-protective effects ascribed to their precursor 50 , 51 . The discovery that high levels of neuroglobin (NGB), an endogenous neuroprotective globin, are active against several brain injuries, including neurodegeneration, hypoxia, ischaemia, toxicity, and nutrient deprivation prompted us to evaluate the effect of different concentrations of Ptb and their fluorescent derivatives in SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of any toxics effects of Ptb fluorescent derivatives ( 1 , 2 ) raised the question if these compounds still maintain some of neuro-protective effects ascribed to their precursor 50 , 51 . The discovery that high levels of neuroglobin (NGB), an endogenous neuroprotective globin, are active against several brain injuries, including neurodegeneration, hypoxia, ischaemia, toxicity, and nutrient deprivation prompted us to evaluate the effect of different concentrations of Ptb and their fluorescent derivatives in SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidative enzymes that work to alleviate oxidative stress mainly include GSH and SOD. SOD prevents the formation of hydroxyl radicals by catalyzing the conversion of superradicals to H 2 O 2 (Yan et al., 2021 ). Accumulation of ROS and depletion of antioxidant enzymes may cause secondary brain damage (Chouchani et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…PTE, a natural product with neuronal protection, has a chemical structure similar to that of RES and plays an important role in nervous system diseases. Evidence suggests that PTE can attenuate cerebral ischemia reperfusion injury by inhibiting oxidative stress and neuronal apoptosis ( Zhou et al, 2015 ), modulating microglial activation ( Liu J. et al, 2020 ), and suppressing cyclooxygenase-2 (COX2) ( Yan et al, 2021 ). It is reported that PTE alleviates Aβ 1–42 -induced cognitive dysfunction by inhibiting oxidative stress in SH-SY5Y cells ( Xu et al, 2020 ) and regulating the phosphatidylinositol 3-kinase (PI3K)/AKT pathway in PC12 cells ( Fu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%